Tillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/Double-Crop Soybean Rotation - D. W. Sweeney; D. Ruiz-Diaz (Kansas Agricultural Experiment Station Research Reports, 2019)
In 2018, adding nitrogen (N) greatly improved average wheat yields with about a 10% increase with knife compared to broadcast application methods. Even though tillage did not affect wheat yields, soybean yield was about 10% greater with no-till.
Keywords: tillage; no-till; nitrogen placement; corn; wheat; soybean